Expanding the vision of entrepreneurial universities: a case study of UNIRIO in Brazil - Mariza Almeida; Douglas Santos; Luiziana Arag\~ao; Gabriel Nogueira; Andrea Bonifácio; Bruno Sim\~oes; Branca Terra (Triple Helix, 2016)
This paper aims to study a set of entrepreneurial activities at a public university and the interaction with other universities, the business sector and government at Federal University of the State of Rio de Janeiro (UNIRIO), Brazil. The study sought an understanding of the dynamics and results of the research activities, the interaction with various organizations and the establishing of commercial, social, cultural and civic entrepreneurship developed by UNIRIO's research groups. Analysis of the activities related to entrepreneurship, in a broad sense, offers the possibility of shedding light on less appreciated but equally important aspects of the activities performed by universities, representing an initiative focused on social and humanistic activities. It is this set of endeavors, aimed at the commercialization of technology and appropriation of knowledge, along with others aimed at creating social value, that comprise the entrepreneurial university.
Keywords: 330; Innovation policy; Triple helix; Entrepreneurial university; Research groups; University-industry-government interaction